Strategies for the production of dsRNA biocontrols as alternatives to chemical pesticides - Hough, James; Howard, John D.; Brown, Stephen; Portwood, David E.; Kilby, Peter M.; Dickman, Mark J. (Frontiers in Bioengineering and Biotechnology, 2022)
Current crop pest control strategies rely on insecticidal and fungicidal sprays, plant genetic resistance, transgenes and agricultural practices. However, many insects, plant viruses, and fungi have no current means of control or have developed resistance against traditional pesticides. dsRNA is emerging as a novel sustainable method of plant protection as an alternative to traditional chemical pesticides. The successful commercialisation of dsRNA based biocontrols for effective pest management strategies requires the economical production of large quantities of dsRNA combined with suitable delivery methods to ensure RNAi efficacy against the target pest. A number of methods exist for the production and delivery of dsRNA based biocontrols and here we review alternative methods currently employed and emerging new approaches for their production. Additionally, we highlight potential challenges that will need to be addressed prior to widespread adoption of dsRNA biocontrols as novel sustainable alternatives to traditional chemical pesticides.